Perhitungan Break Event Point (BEP) pada Usaha Mikro Kecil Menengah (UMKM) “Yuli Bakery” Jember - Maram, Ghaitsul; Susanto, Andri Mardi; Suwarso, Suwarso (ACCOUNT (Journal of Accounting and Finance), 2024)
The study is to describe the calculation of Break Even Point in Micro, Small, and Medium Enterprises (MSME) “Yuli Bakery". The break even point calculations are an important tool in financial management to determine a breaking point. The study used the quantitative if approach, based on the operational costs associated with MSME "Yuli Bakery". This research method included the collecting of data from the interview's notes, observation and documentation on the "Yuli Bakery". The type of data used are secondary data that include a company profile, a cost data, production data, a product sale price, and sales data of a product. The results showed that the calculation of Break Even Point (BEP) occurred when MSME "Yuli Bakery" sold 565 units of products.